Causes and Consequences of the Formation and Development of the Institute of Professional Accountants - Valerii Zhuk; Serhii Ostapchuk; Natalia Golub (Облік і фінанси, 2023)
Assumptions about the absence of a future in the accounting profession in the era of digitalization determine the need to assess the fundamental guidelines for its further development. The institutional theory considers accounting as an important socio-economic institute and the accountant as an informal carrier of this financial institution. Today, in practice, accounting occupies an important place not only in managing economic entities but also in adopting state decisions and decisions on the capital market. The article's purpose is to deeply investigate the phenomenon of the institute of professional accountants, the historical prerequisites of its formation and, most importantly, its influence on the future of the accounting profession. The results of the study show that an accountant can be considered a representative of the profession (institute) if he possesses knowledge, skills and adheres to professional ethics. A clear observance of these qualities is formed as the economy develops and reaches its heyday only with the formation of the professional accounting movement. The article also analyzes the history of the formation of accounting professional organizations. It was revealed that today the formation of such organizations takes place under the supervision and control of the state. Although accounting professional organizations have a national identity, their development is determined by factors of globalization. Formally, the "institute of accountants" is always present everywhere in the broader consideration of the accounting phenomenon. "Institute of accountants" and "institute of professional accountants" differ in their internal and external content maturity. For most countries, including Ukraine, the development of the institute of professional accountants is based on borrowing the "rules of the game" and organizational practices from more developed countries. Institutional paradigm and theory create fundamental guidelines for substantiating the development of accounting and the accounting profession.